Increment in plasma leptin level while decrement in ghrelin levels in epileptic patients with Depakine therapy - Aydin, Suleyman; Yoldas, Tahir (Amer Soc Biochemistry Molecular Biology Inc, 2004)
[Abstract Not Available]